Pengaruh Pemahaman Akuntansi dan Software Akuntansi Terhadap Kualitas Laporan Keuangan UMKM di Kabupaten Sleman Yogyakarta - Nugraeni; Tunjanan, Falens (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
MSMEs are Micro, Small, and Medium Enterprises managed by any agency, organization, or individual. In managing MSMEs, it is necessary to have accounting information which is the basis for the management and development of MSMEs. Financial Statements are useful financial information for various things, including finding out the performance of MSME business activities and becoming the basis for MSMEs in making decisions. The purpose of this study is to identify various factors that affect the quality of MSME financial statements. This study was conducted in Sleman Regency, Yogyakarta, with data collection using purposive sampling techniques and, slovin formula as a determinant of the number of samples used, so that 44 MSMEs were involved as samples. This study adopts the Use-Decision theory which explains how financial statements can be beneficial to its users. The data was analyzed using the 2021 version of SPSS, the data analysis used was a classical assumption test and a hypothesis test, there were three variables used, namely the quality of financial statements, as well as accounting understanding and accounting software as variables. The result of this research that has been carried out is that accounting understanding does not affect the quality of financial statements while accounting software affects the quality of financial statements.